2013
DOI: 10.1590/s0102-33062013000100010
|View full text |Cite
|
Sign up to set email alerts
|

Mixed rain forest in southeastern Brazil: tree species regeneration and floristic relationships in a remaining stretch of forest near the city of Itaberá, Brazil

Abstract: Th e aim of this work was to evaluate the fl oristic composition, richness, and diversity of the upper and lower strata of a stretch of mixed rain forest near the city of Itaberá, in southeastern Brazil. We also investigated the diff erences between this conservation area and other stretches of mixed rain forest in southern and southeastern Brazil, as well as other nearby forest formations, in terms of their fl oristic relationships. For our survey of the upper stratum (diameter at breast height [DBH] ≥ 15 cm)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
7

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 14 publications
0
7
0
7
Order By: Relevance
“…The scarcity of data in the literature on the forest understory is even greater for the shrub layer than for the herb layer, because it is common to perform a joint analysis of the floristic composition of the "tree-shrub" community, which includes, in addition to shrubs, the transient community of juvenile individuals of canopy species and adult trees of the upper strata. In some studies, juvenile individuals of tree species have been classified as shrubs (Ribeiro et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The scarcity of data in the literature on the forest understory is even greater for the shrub layer than for the herb layer, because it is common to perform a joint analysis of the floristic composition of the "tree-shrub" community, which includes, in addition to shrubs, the transient community of juvenile individuals of canopy species and adult trees of the upper strata. In some studies, juvenile individuals of tree species have been classified as shrubs (Ribeiro et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The major contribution of vines to the community structure of the understory in Itaberá is related to the greater abundance of deciduous trees in the canopy at that location (Ribeiro et al 2013), which results in different conditions of light within the forest, a true environmental mosaic not only for tree regeneration but also for the resident community of the understory (Souza et al 2010;. Given these apparent advantages, Villagra & Romaniuc-Neto (2010) showed that even a small vegetation fragment, such as that evaluated in Itaberá, can harbor the same vine species richness as do large areas of contiguous forest.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations